2016
DOI: 10.1002/jhbp.394
|View full text |Cite
|
Sign up to set email alerts
|

Current role of percutaneous transhepatic gallbladder aspiration: from palliative to curative management for acute cholecystitis

Abstract: Percutaneous transhepatic gallbladder aspiration can be a useful alternative for most patients with AC, including those at high risk. Elective cholecystectomy can be performed safely regardless of the timing of PTGBA or surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…There are several possibilities for this reason as follows: (1) based on our experience and previous literature, there might be the possibility that the PTGBA group included mild or moderate grade cholecystitis; (2) lavage of gallbladder using saline was more effective than simple drainage; and (3) rapid decompression of gallbladder contents by aspiration causes the release of impacted stone at the neck and even cystic duct (going back in gallbladder). Interestingly, the latest large cohort study in a high volume center where expertise of PTGBA is present, revealed that 263 (95.6%) of 275 high risk patients (aged ≥80 years and/or with American Society of Anesthesiologists score III to IV and/or performance status 3 to 4) showed recovery after PTGBA . These data suggest that 75% and 96.2% clinical success in 3 and 7 days, respectively is reasonable in the PTGBA group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several possibilities for this reason as follows: (1) based on our experience and previous literature, there might be the possibility that the PTGBA group included mild or moderate grade cholecystitis; (2) lavage of gallbladder using saline was more effective than simple drainage; and (3) rapid decompression of gallbladder contents by aspiration causes the release of impacted stone at the neck and even cystic duct (going back in gallbladder). Interestingly, the latest large cohort study in a high volume center where expertise of PTGBA is present, revealed that 263 (95.6%) of 275 high risk patients (aged ≥80 years and/or with American Society of Anesthesiologists score III to IV and/or performance status 3 to 4) showed recovery after PTGBA . These data suggest that 75% and 96.2% clinical success in 3 and 7 days, respectively is reasonable in the PTGBA group.…”
Section: Discussionmentioning
confidence: 99%
“…Although PTGBD is still first‐line therapy of decompression of enlarged gallbladder, recently, there have been several suboptimal alternatives to PTGBD. Percutaneous transhepatic gallbladder aspiration (PTGBA) using a 19‐gauge or 22‐gauge aspiration needle is a simple decompression method . Another alternative is endoscopic transpapillary gallbladder decompression by means of endoscopic retrograde cholangiopancreatography (ERCP) technique including endoscopic naso‐gallbladder drainage (ENGBD) and gallbladder stenting (EGBS) in acute cholecystitis.…”
Section: Introductionmentioning
confidence: 99%
“…Although PTGBA without catheter placement appears to be a simple and easy decompression method, aspiration could be unsuccessful because of replacement of bile with dense biliary sludge or pus (RCT) , (OS) . Therefore, PTGBA should not be recommended as a standard procedure for all patients with AC.…”
Section: Percutaneous Transhepatic Gallbladder Drainagementioning
confidence: 99%
“…Since then, TG13 stated that PTGBD should be recommended as the first alternative to cholecystectomy in such patients . However, some studies have evaluated the usefulness of percutaneous transhepatic gallbladder aspiration (PTGBA) without catheter placement as a simple decompression method . Another alternative procedure is endoscopic gallbladder drainage, which can be performed using either a transpapillary or transmural approach.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found procedure-related complications in elderly patients with AC were only 7.16%, comparable to those of previous reports. [20] Although urgent cholecystectomy (within 72 hours from symptom onset) has been proposed as a de nitive treatment for symptomatic gallbladder disease, [21] routine cholecystectomy in an emergency setting can be challenging. Rather, gallbladder puncture is a better choice for surgeons with less experience.…”
Section: Discussionmentioning
confidence: 99%